2005
DOI: 10.1016/j.jala.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Screening Assay for Determination of Aqueous Equilibrium Solubility Enabling SPR Study During Drug Lead Optimization

Abstract: A queous solubility is one of the most critical physicochemical properties to be determined in the process of drug lead optimization. Particularly, an equilibrium solubility method is highly valuable to the study of structure property relationship (SPR), while meeting the needs of analytical sensitivity, reproducibility, and throughput. In this report, an automated solubility assay in a 96-well library format was designed and developed by means of robotic liquid handling, centrifugal separation, and HPLC-UV qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The details of the plate design have been described previously. 16 Using a robotic liquid handling system (Symyx Technologies), the supernatant was removed and 700 :L of sterile water was added to each well to wash the pellet. The plate was inverted several times and centrifuged prior to removal of water using the liquid handler.…”
Section: Solubility Plate Design and Preparation For Concentration Mementioning
confidence: 99%
“…The details of the plate design have been described previously. 16 Using a robotic liquid handling system (Symyx Technologies), the supernatant was removed and 700 :L of sterile water was added to each well to wash the pellet. The plate was inverted several times and centrifuged prior to removal of water using the liquid handler.…”
Section: Solubility Plate Design and Preparation For Concentration Mementioning
confidence: 99%
“…The system consisted of a solid dispensing robot, a liquid handling robot and an Agilent 1100 HPLC [31,32]. The organic modifiers chosen for solubility screening were MeOH, EtOH, IPA, MeCN and DME containing 0.2% DEA.…”
Section: Determination Of Solubility In Organic Modifiers Using the Smentioning
confidence: 99%
“…Several miniaturized platforms with different throughput have been evaluated to assess equilibrium solubility using Uni-Prep filter chamber [50] [51], circulation pump [52], and vials [53] [54]. In 2007, Zhou et al [48] reported a true HT and miniaturized equilibrium solubility approach utilizing mini-prep vials and fast HPLC.…”
Section: Solubility and Dissolutionmentioning
confidence: 99%